Strategi Pengembangan Rainbow Rafting Untuk Meningkatkan Potensi Sport Tourism Kecamatan Randudongkal Kabupaten Pemalang - Inayah Agustina Sunarto (Journal of Physical Activity and Sports (JPAS), 2021)
This research is a descriptive study with a qualitative approach using a SWOT analysis. Research subjects are managers, employees and tourists of Rainbow Rafting. Collecting data using interviews, observation and documentation. Data analysis uses methods that are carried out continuously with data reduction, data presentation and conclusion drawing. The results of this study indicate that: Strategies that can be used by Rainbow Rafting based on the SWOT matrix are: 1) Ensuring the safety of goods and tourist safety, 2) Improving good service, 3) Using electronic media as a means of promotion, 4) Always paying attention to the condition of the facility, 5) Increase social media promotion, 6) Improve attractive and creative facilities, 7) and always protect the basecamp and river environment. The data is in accordance with the results that have been designed to form a strategy for developing Rainbow Rafting.